TUBUH SEBAGAI SUBYEK DALAM DUNIA: KAJIAN ATAS SKEMA TUBUH DAN INTENSIONALITAS MOTORIK MENURUT MERLEAU-PONTY - Kuntjoro, Antonius Puspo (UI Scholars Hub, 2025)
This article explores Maurice Merleau-Ponty's thought on the role of the body in shaping human experience, focusing on two key concepts: body schema and motor intentionality. Contrasting with the dualistic approach of modern Western philosophy that separates body and consciousness, Merleau-Ponty asserts that the body is not merely an object but an active subject in the world. The body schema is understood as a dynamic and pre-reflective structure that enables individuals to perceive the position and movement of their bodies within a situational space. Motor intentionality, as illustrated through the case of Schneider, shows that the body has the capacity to project meaning and respond directly to the world without cognitive reflection. This writing emphasizes the need to rehabilitate the role of the body in contemporary philosophical discourse, particularly in understanding the human-world relationship holistically.